Dynamic profile of EVs in porcine oviductal fluid during the periovulatory period. Issue 4 (April 2020) - Laezer, Inga; Palma-Vera, Sergio E; Liu, Fan; Frank, Marcus; Trakooljul, Nares; Vernunft, Andreas; Schoen, Jennifer; Chen, Shuai
Abstract : In mammals, around the time of ovulation, the hormonal profile dynamically changes in synchrony with reproductive events occurring in the oviduct, that is, sperm arrival, fertilization, and early embryo development. Extracellular vesicles (EVs) have been recently recognized as key components of the embryonic milieu; however, composition and function of oviductal EVs during this crucial period remains to be further explored. Therefore, we initially characterized EVs from porcine oviductal fluid specifically around the critical ovulation window: that is, estrus (E), late estrus (LE, day of expected ovulation), post ovulation (PO), and additionally diestrus (D). Total EV numbers gradually rose from D to E, LE and PO ( P  < 0.05), which corresponded to the total EV protein amount ( P  < 0.05). Strikingly, the mean size of EVs in PO was significantly smaller than in E and LE groups, which also had a lesser proportion of small EVs ( P  < 0.05). The EV protein cargoes during the periovulatory period were further analyzed by mass spectrometry. Qualitative analysis detected 1118 common proteins, which are most enriched in the cellular component of EVs/exosomes. Hierarchical clustering indicated similar protein profile within the biological replicates, but large discrepancy among stages. Further quantitative analysis discovered 34 and 4 differentially expressed proteins in the comparison between E and PO and in the comparison between E and LE, respectively. The dynamic EV protein profile together with the quick adaption in EV size and quantity suggests that porcine oviductal EV secretion are under the hormonal influence during the estrus cycle.